2015
DOI: 10.1007/s11665-015-1636-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment on Corrosion Resistance of High-Velocity Oxygen-Fuel Sprayed WC-17Co Coatings on 42CrMo Steel

Abstract: The influence of heat treatment from 500 to 1100°C on the 5 wt.% H 2 SO 4 solution-induced corrosion resistance of high-velocity oxygen-fuel sprayed WC-17Co coatings on 42CrMo steel was investigated, by using x-ray diffractometer (XRD), scanning electron microscopy (SEM)-energy-dispersive spectrometer (EDS), and polarization curve methods. XRD analysis showed decrease in W 2 C phase intensity with recrystallization of amorphous Co and generation of new Co 3 W 3 C and Co 6 W 6 C phases with heat treatment. Poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The corrosion mechanism of the coating is shown in Figure 9, the phosphate sealing treatment makes it more difficult for the corrosion medium to reach the coating/substrate interface, and effectively reduces the coating defects, such as porosity and residual cracks, which can effectively slow down the corrosion process of the coating 36,37 . For immersion corrosion, the formation of macrocorrosion morphology of the coating is mainly the result of many factors, and the corrosion mechanism is more complex 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion mechanism of the coating is shown in Figure 9, the phosphate sealing treatment makes it more difficult for the corrosion medium to reach the coating/substrate interface, and effectively reduces the coating defects, such as porosity and residual cracks, which can effectively slow down the corrosion process of the coating 36,37 . For immersion corrosion, the formation of macrocorrosion morphology of the coating is mainly the result of many factors, and the corrosion mechanism is more complex 38 …”
Section: Resultsmentioning
confidence: 99%
“…36,37 For immersion corrosion, the formation of macrocorrosion morphology of the coating is mainly the result of many factors, and the corrosion mechanism is more complex. 38 F I G U R E 6 Immersion corrosion rates of the coatings before and after sealing…”
Section: Microhardness Immersion Corrosion Weight Loss and Mechanism ...mentioning
confidence: 99%
“…High-velocity oxygen fuel spraying technology has replaced traditional plasma spraying in many fields due to its advantages, including lower operating temperatures, reduced economic costs, and higher spraying efficiency [8]. Sun et al [9] prepared WC-17Co coatings on the surface of 42CrMo steel using the surface engineering process of high-velocity oxygen fuel spraying. The impact of heat treatment on the coatings was explored across a temperature range spanning from 500 to 1100 • C. The results demonstrated a reduction in W 2 C phase intensity as amorphous Co underwent recrystallization, accompanied by the formation of new phases such as Co 3 W 3 C and Co 6 W 6 C upon heat treatment.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Sun et al [9] demonstrated that the impact of heat treatment temperature on the corrosion resistance of coatings could be attributed to three factors: the internal stress state, the microstructure and phase structure of the bonded phases, and, most critically, the original presence of pores and cracks. They investigated the effect of heat treatment on the corrosion performance of WC-17Co coatings prepared by LC.…”
Section: Improving Defects and Microstructurementioning
confidence: 99%
“…The 42CrMo alloy steel has been widely used in drilling industry. With the increasing depth of drilling, the salt water of drilling fluid will be continuously injected and tools of downhole drilling will be seriously corroded [1][2]. In general, the cost of replacing parts is quite high, and on the contrary, using remanufacturing repair technology to improve the performance of workpieces is an effective means.…”
Section: Introductionmentioning
confidence: 99%